Filsafat Manusia Ibnu Arabi - Happy Susanto (TSAQAFAH, 2014)
The aims of this article is to investigating the philosophy of human being Ibn Arabi. The philosophy of human being can define as of study the nature of human being, that is the essential characteristic that make up human being and their manifestations and implications. Ibnu Arabi is one of the philosopher that concern to discuss about divine root of human creation. Arabi focuses upon reality itself, and reality is Wujûd, that is, being, existence, or that which is found. Wujûd is the Real or al-haqq, which is another name for God. In itself, Wujûd is concealed and nonmanifest. In other words, it is the Hidden Treasure. However, Wujûd loved to be known, so it created the universe in order to be known. Those who know Wujûd in a full sense are true human beings, or perfect human being (al-insan al-kamil). But people cannot know Wujûd unless wujûd makes itself known to them. It makes itself known by manifesting itself in three basic ways: through the universe, through the self, and through scripture. Scripture, the Qur’an in particular, is the key that opens the door to the universe and the self. Prefect human being is linked between the two diametrically opposed aspects of the unique divine reality. Netheir an animal or an angle, man hovers between the world of corruption and the world of immutability. By virtue of his intermediary position, man becomes a microcosmic reality in which God contemplates Himself in the most eduquate form. Prefect man is that human individual who has perfectly realized that full spiritual potential of the human state, who has realized in himself and his experience the Oneness of Being than underlies all the apparent multiplicity of existence.